2001
DOI: 10.1067/mcp.2001.115445
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the pharmacokinetic properties of Harpagophytum extracts and their effects on eicosanoid biosynthesis in vitro and ex vivo

Abstract: Our observations strongly indicate a close relation between serum harpagoside levels and the inhibition of leukotriene biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 12 publications
(20 reference statements)
1
44
1
1
Order By: Relevance
“…Compared with the rest of the products, the Boots tablets contained low amounts of glycosides with only 0.0006 mmol/day of 8-O-p-coumaroyl harpagide (4), which previously exhibited a good antiinfl ammatory action in ex vivo porcine skin (Abdelouahab and Heard, 2008b). Also, harpagoside (1) which is believed to be a key ingredient in the extract (Baghdiakin 1997;Loew et al, 2001;Tippler et al, 1997) was present at very low levels in formulations B, D, F with proportions that that do not meet the requirement of the European Pharmacopoeia for the standardized H. procumbens extract (not less than 1.2% of the dried root). Interestingly, these formulations appear to contain higher relative proportions of harpagide (2).…”
Section: Resultsmentioning
confidence: 98%
“…Compared with the rest of the products, the Boots tablets contained low amounts of glycosides with only 0.0006 mmol/day of 8-O-p-coumaroyl harpagide (4), which previously exhibited a good antiinfl ammatory action in ex vivo porcine skin (Abdelouahab and Heard, 2008b). Also, harpagoside (1) which is believed to be a key ingredient in the extract (Baghdiakin 1997;Loew et al, 2001;Tippler et al, 1997) was present at very low levels in formulations B, D, F with proportions that that do not meet the requirement of the European Pharmacopoeia for the standardized H. procumbens extract (not less than 1.2% of the dried root). Interestingly, these formulations appear to contain higher relative proportions of harpagide (2).…”
Section: Resultsmentioning
confidence: 98%
“…In vitro studies demonstrated that Hp extracts were able to suppress the biosynthesis of cysteinyl-leukotrienes (Cys-LT; LTC 4 , LTD 4 and LTE 4 ) and TXB 2 when whole blood was stimulated with the calcium ionophore, A23187 (Tippler et al, 1997;Loew et al, 2001). Of further interest was that although the entire extract proved more effective than pure harpagoside alone, the extent of eicosanoid inhibition was found to be as a direct function of the harpagoside concentration, indicating that harpagoside may be the most pharmacologically active component.…”
Section: Preclinical Research (In Vitro and Ex Vivo)mentioning
confidence: 99%
“…A prerequisite for the analgesic and antiphlogistic effect is the inhibition of eicosanoid biosynthesis. In vitro studies showed that the inhibition of biosynthesis of cysteinyl-LT and thromboxane B 2 strongly depends on the extraction method, the extraction solvent and the harpagoside content (Loew et al, 2001). Extract fractions containing harpagoside had inhibitory effects on in vitro eicosanoid biosynthesis, whereas fractions without harpagoside had no effects or even stimulated cysteinyl-LT biosynthesis.…”
Section: Bioequivalence Of Herbal Products 707mentioning
confidence: 99%